Prevalência e fatores de risco associados à coinfecção com vírus da hepatite B (HBV) em pacientes HIV positivos no estado do Piauí - Aragão, Ana Luísa Eulálio Dantas (2011)
The coinfection between the Human Immunodeficiency Virus (HIV) and Hepatitis B Virus (HBV) has the same transmission factors and consequently the associated risk factors explain the high prevalence of these infectious agents in our midst. This study estimated the prevalence of HIV and HBV coinfection and described the individual characteristics that act as risk factors for acquisition of coinfection, in order to use this information for advice. The sample was composed of 805 patients infected with HIV in the state of Piauí who sought the LACEN-PI for monitoring viral load and CD4 + T lymphocytes. The prevalence of Hepatitis B (HB), using the marker anti-HBc, and was 29.3% for HBsAg this value was 2.5%. The prevalence of Anti-HBc was 38.3% aged over 40 years, 38.6% for males, 31.9% among unmarried, 47.7% among retirees, 50.7% among who reported a history of jaundice, 54% among those who were diagnosed with hepatitis, 40.7% among those passing through reformatory or prison, 38.1% among non-intravenous drug users, 35.7% with sexual contact with illicit drug users, 48.8% with a preference among homosexual / bisexual, 44.9% among those who reported having sexual contact with a prostitute rare, 37.1% among those who had STD and 31.4% for those with viral load below 10,000 copies / mL of blood. We observed statistical significance between variables and the frequency of positive anti-HBc. The information in this work could be used in combat, counseling and prevention of advancement, the number of HB cases in HIV positive patients.